MTI Website Quality Improvement as A Strategy to Increase Webometric Ranking - Ristono, Agus; Lucitasari, Dyah Rahmawati; Astanti, Yuli Dwi; Rahmawati, Berty Dwi; Kasih, Puji handayani (RSF Conference Series: Business, Management and Social Sciences, 2021)
The website is one of the communication platforms used by a university to provide information, especially to students and generally to the public. In addition to increasing service satisfaction, improving the quality of the website is also one of the benchmarks for the quality of education in a university. Webometrics is one of the world-class university website ranking metrics. Webometrics has several metrics that can describe the quality of a website. The UPNVY MTI Department is one of the study programs at UPNVY, which is committed to participating in improving the university’s webometrics ranking. To improve service quality and website ranking on webometrics, it is necessary to formulate a strategy to improve the website quality. This study conducts a SWOT analysis in order to design strategies that can be carried out to improve the quality of the MTI UPNVY website. The results showed that there were eight strategies that could be implemented. The most important strategy to be implemented is to establish a special team to manage the MTI UPNVY website on a regular and up-to-date.